Patterns of Choroidal Deepening in Highly Myopic Eyes with Dome-Shaped Macula. (2nd August 2020) - Zhao, Xiujuan; Lian, Ping; Li, Songshan; Liu, Bingqian; Ding, Xiaoyan; Lu, Lin
ABSTRACT: Purpose: To investigate the patterns and characteristics of choroidal deepening (CD) in highly myopic eyes with a dome-shaped macula (DSM). Methods: A retrospective analysis of vertical and horizontal optical coherence tomography (OCT) scans across the central fovea was conducted. An inward bulge greater than 50μm at either the vertical or horizontal OCT images of the macula was defined as DSM and was analyzed. Results: Among the 155 eyes, a vertical oval-shaped DSM was present in eight eyes (5.16%), a horizontal oval-shaped in 102 eyes (65.81%), and a round DSM in 45 eyes (29.03%). Vertical oval-shaped DSM exhibited the longest axial length (AL) and the largest dome base among the three types ( P < .05). The CD in DSM was classified into three distinct patterns: sub-dome choroidal deepening (SDCD), peri-dome choroidal deepening (PDCD), and the absence of CD according to the ratio of peri-dome choroidal thickness (CT) to sub-dome CT. Overall, no significant difference was found in age, AL, best corrected visual acuity (BCVA), dome base, dome height and choroidal vascularity among the three patterns of CD. However, the eyes with SDCD showed the thickest CT and the largest total choroidal area and vascular area. Conclusions: Three morphological patterns of CD were found in highly myopic eyes with DSM. These three patterns should be considered when discussing CT in highly myopic eyes.